Public Perception of Covid-19 Vaccination in Merawang Village, Lingga District, Lingga Regency - Agung Yuda Pratama; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
This study investigates the perception of the people of Merawang Village, Lingga Subdistrict towards the COVID-19 vaccine. Despite the government's efforts to accelerate vaccination as a way to combat the coronavirus outbreak, many people have not yet received the vaccine due to confusing information about its side effects. This study aims to examine the community's perception towards the vaccine in order to shed light on this issue. The research methodology employed is descriptive qualitative, with 13 informants and data collection techniques such as interviews, documentation, and field observations. The results suggest that the confusing information about the vaccine's side effects has affected people's knowledge and attitudes, leading to increasing hesitation in getting vaccinated. Social interactions also play a role in shaping these perceptions. However, the government's policy requiring people to go through administration and travel agents has motivated some people to get vaccinated. Overall, this study provides valuable insights into the challenges faced in vaccine acceptance and the need for clear communication to address misconceptions.